Internet censorship detected in Venezuela (Venezuela) - Voidly (2026)
CRITICAL severity censorship detected in Venezuela. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: VE-2026-0400
Keywords: censorship; VE; censorship; critical